AN ANALYSIS OF STUDENTS’ MOTIVATION IN LEARNING ENGLISH AFTER GIVEN REWARDS AT THE EIGHT GRADE STUDENTS’ OF SMPN 3 RAMBAH - Evi Kasyulita; Armelida (JEE (Journal of English Education), 2019)
The purpose of this research was to find out the eight grades students’ motivation in learning English after given rewards at the SMPN 3 Rambah. The students’ was low motivation in learning English. This research was design a descriptive qualitative research and there were 2 instruments were used in collecting the data. There are 2 instruments that is questionnaire and interview. The researcher used three classes. There were 60 samples joined in the research. The purpose of giving the questionnaire was to find out the students motivation in learning English after given reward and interview given was purposed to find out the students’ opinion of their English learning. The result of the research in the questionnaire showed that from 60samples of the research, there were 57 students can be classified have strong motivation in learning English after given rewards and there 3 students can be classified have fair motivation. The calculation was taken from the students’ answer in questionnaire and converted to the numeric score on Likert scale. Based on the finding of this research, the questionnaire score and classify it. The researcher found that the average of students questionnaire score was 78,8 and it means that their motivation averagely can be classified Good categories.